2016
DOI: 10.1021/acs.biochem.6b00553
|View full text |Cite
|
Sign up to set email alerts
|

Base Excision Repair of N6-Deoxyadenosine Adducts of 1,3-Butadiene

Abstract: The important industrial and environmental carcinogen, 1,3-butadiene (BD), forms a range of adenine adducts in DNA, including N6-(2-hydroxy-3-buten-1-yl)-2′-deoxyadenosine (N6-HB-dA), 1,N6-(2-hydroxy-3-hydroxymethylpropan-1,3-diyl)-2′-deoxyadenosine (1,N6-HMHP-dA), and N6,N6-(2,3-dihydroxybutan-1,4-diyl)-2′-deoxyadenosine (N6,N6-DHB-dA). If not removed prior to DNA replication, these lesions can contribute to A → T and A → G mutations commonly observed following exposure to BD and its metabolites. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Since other N 1 -dIno adducts form Hoogstein base pairs and flip outside the DNA helix, it is possible that our POBand PHB-N 1 -dIno adducts are prime targets for base excision repair or other DNA repair mechanisms. 31,44,45 In our preliminary studies of the reaction of NNKOAc with calf thymus DNA, we observed an HPLC peak which decreased relatively rapidly with time, as peaks corresponding to N 6 -POB-dAdo and N 1 -POB-dIno increased (data not shown). We presume that this peak was N 1 -POB-dA.…”
Section: ■ Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Since other N 1 -dIno adducts form Hoogstein base pairs and flip outside the DNA helix, it is possible that our POBand PHB-N 1 -dIno adducts are prime targets for base excision repair or other DNA repair mechanisms. 31,44,45 In our preliminary studies of the reaction of NNKOAc with calf thymus DNA, we observed an HPLC peak which decreased relatively rapidly with time, as peaks corresponding to N 6 -POB-dAdo and N 1 -POB-dIno increased (data not shown). We presume that this peak was N 1 -POB-dA.…”
Section: ■ Discussionmentioning
confidence: 93%
“…Since other N 1 -dIno adducts form Hoogstein base pairs and flip outside the DNA helix, it is possible that our POB- and PHB- N 1 -dIno adducts are prime targets for base excision repair or other DNA repair mechanisms. 31,44,45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent study, we have shown that BD-dA adducts are rapidly repaired by nuclear extracts from human cells, but the identity of the glycosylase involved is yet to be established. 52 However, the rapid repair hypothesis may be insufficient to explain why three of the BD-dA lesions were genotoxic but not mutagenic.…”
Section: Discussionmentioning
confidence: 99%
“…EB forms covalent adducts with DNA including N 6 -(2-hydroxy-3-buten-1-yl)-2′-deoxyadenosine, 1-(1-hydroxy-3-buten-2-yl)-adenine, 1-(2-hydroxy-3-buten-1-yl)-adenine, 3-(1-hydroxy-3-buten-2-yl)-adenine, 3-(2-hydroxy-3-buten-1-yl)-adenine, 7-(2-hydroxy-3-buten-1-yl)-adenine (EB-GI), and 7-(1-hydroxy-3-buten-2-yl)­guanine (EB-GII). These adducts can cause DNA polymerase stalling and misreading during DNA replication, leading to toxicity and mutations. , If present in a tumor suppressor gene or a proto-oncogene, such mutations can lead to unrestricted cell growth and the development of cancer. , …”
Section: Introductionmentioning
confidence: 99%